Pulsatility of Lenticulostriate Arteries Assessed by 7 Tesla Flow MRI—Measurement, Reproducibility, and Applicability to Aging Effect - Schnerr, Roald S.; Jansen, Jacobus F. A.; Uludag, Kamil; Hofman, Paul A. M.; Wildberger, Joachim E.; van Oostenbrugge, Robert J.; Backes, Walter H. (Frontiers in Physiology, 2017)
Characterization of flow properties in cerebral arteries with 1.5 and 3 Tesla MRI is usually limited to large cerebral arteries and difficult to evaluate in the small perforating arteries due to insufficient spatial resolution. In this study, we assessed the feasibility to measure blood flow waveforms in the small lenticulostriate arteries with 7 Tesla velocity-sensitive MRI. The middle cerebral artery was included as reference. Imaging was performed in 5 young and 5 old healthy volunteers. Flow was calculated by integrating time-varying velocity values over the vascular cross-section. MRI acquisitions were performed twice in each subject to determine reproducibility. From the flow waveforms, the pulsatility index and damping factor were deduced. Reproducibility values, in terms of the intraclass correlation coefficients, were found to be good to excellent. Measured pulsatility index of the lenticulostriate arteries significantly increased and damping factor significantly decreased with age. In conclusion, we demonstrate that blood flow through the lenticostriate arteries can be precisely measured using 7 Tesla MRI and reveal effects of arterial stiffness due to ageing. These findings hold promise to provide relevant insights into the pathologies involving perforating cerebral arteries.